Combination of anti-tuberculosis drugs with vitamin C or NAC against different Staphylococcus aureus and Mycobacterium tuberculosis strains. (April 2016) - Khameneh, Bahman; Fazly Bazzaz, Bibi Sedigheh; Amani, Alireza; Rostami, Javad; Vahdati-Mashhadian, Nasser
Abstract: Backgrounds: Hepatotoxicity due to anti tuberculosis drugs, rifampin and isoniazid, is a major problem in tuberculosis patients. Vitamin C, an antioxidant, and N-acetyl cysteine (NAC), a scavenger of active metabolites, reduce the hepatotoxicity. The aim of present study was to investigate the effect of vitamin C and NAC individually on the antibacterial activity of anti tuberculosis drugs against Mycobacterium tuberculosis and Staphylococcus aureus strains. Methods: The MICs of each compound against all strains were determined in 96 wells plate. Rifampin was tested at serial two fold concentrations alone or in combination with NAC or vitamin C. Results: The MIC of rifampin against different strains of S. aureus was 0.008–0.032 μg/ml. The MIC of rifampin and isoniazid against M. tuberculosis strains were 40 and 0.2 μg/ml, respectively. Vitamin C and NAC had no antibacterial activity against all strains. MIC of rifampin was reduced two fold by combination with vitamin C for all S. aureus strains, while NAC did not affect the antibacterial activity of rifampin. Vitamin C and NAC had remarkable effects on the antibacterial activity of anti-tuberculosis drugs against M. tuberculosis . Conclusions: Synergistic effects were observed between rifampin or isoniazid and vitamin C against all tested strains. However, combination therapy of rifampin and isoniazid with NAC was not being effective. This study highlighted the advantages of combination of anti-tuberculosis drugs and vitamin C to eradicate the microbial infections. Highlights: Combination therapy of rifampin with vitamin C was effective approach to combat staphylococcal infections. Synergistic effects were observed between rifampin or isoniazid and vitamin C against Mycobacterium tuberculosis strains. NAC did not affect the antibacterial activity of anti-tuberculosis drugs.